Indigofera himachalensis (Fabaceae: Indigofereae), a new species from Himachal Pradesh, India - Pandey, Arun K.; Chauhan, Vibha; Pandey, Arun K.; Schaefer, Hanno (Phytotaxa, 2013)
Indigofera himachalensis, a new species of Fabaceae is described from Himachal Pradesh, India. It differs from I. heterantha in having longer and sparsely adpressed hairy pods and larger seeds that are greater in number per pod with a reticulo-rugulate pattern of the spermoderm.